2017
DOI: 10.1126/scitranslmed.aal2029
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tau antibody administration increases plasma tau in transgenic mice and patients with tauopathy

Abstract: Tauopathies are a group of disorders in which the cytosolic protein tau aggregates and accumulates in cells within the brain, resulting in neurodegeneration. A promising treatment being explored for tauopathies is passive immunization with anti-tau antibodies. We previously found that administration of an anti-tau antibody to human tau transgenic mice increased the concentration of plasma tau. We further explored the effects of administering an anti-tau antibody on plasma tau. After peripheral administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 53 publications
6
47
0
Order By: Relevance
“…The half‐life of Aβ is ~9 hours in the human central nervous system (CNS) as measured in CSF, and we have recently shown that CSF Aβ increases during sleep deprivation from increased production . Tau in the CNS of humans has a half‐life of ~23 days from the time of translation; however, once tau is released into the brain interstitial fluid or CSF, its half‐life is on the order of hours . Therefore, we hypothesize that increased release rather than increased production accounts for the rise in tau concentration during sleep deprivation.…”
Section: Discussionmentioning
confidence: 96%
“…The half‐life of Aβ is ~9 hours in the human central nervous system (CNS) as measured in CSF, and we have recently shown that CSF Aβ increases during sleep deprivation from increased production . Tau in the CNS of humans has a half‐life of ~23 days from the time of translation; however, once tau is released into the brain interstitial fluid or CSF, its half‐life is on the order of hours . Therefore, we hypothesize that increased release rather than increased production accounts for the rise in tau concentration during sleep deprivation.…”
Section: Discussionmentioning
confidence: 96%
“…14 Initial efforts focused on assays that did not differentiate between phosphorylated and unphosphorylated tau. [15][16][17][18][19][20][21] Some studies found that tau in plasma was increased in AD, 16,19,22,23 whereas others found no significant change. 19,24 The Quanterix Human Tau kit (erroneously referred to as "total tau") has been the most widely applied assay used to measure tau in plasma.…”
mentioning
confidence: 99%
“…Targeting numerous other epitopes has been shown to be effective in several studies. These include non-phosphorylated- [27,30,32,41,42,4648,69,70], phosphorylated- [20,24,25,27,29,35,39,43,49], conformational-/oligomeric [20,31,33,34,40,44,45], and a truncated epitope [66,71]. Since these studies have various designs, they cannot be easily compared to identify the best epitopes to target.…”
Section: How Does It Work?mentioning
confidence: 99%